Phonon frequency spectrum of silver under high pressure - Hiba Mohammad Tahir Alhbaite (College of Education for Pure Sciences, 2013)
ABSTRACT Evaluation of effect of pressure on phonon frequency spectrum of silver have been achieved in the present work by analyzing Ag pfs and computing frequencies shift and variation of mode density under high pressure. Computation has been done by combining Vinet EOS with Grüneisen approximation. A good agreement between present results and that reported in literature has been shown.